Engaging deception [large type] - Jennings, Regina (Regina Lea) (Jennings, Regina (Regina Lea). Joplin chronicles, 2023)
"Olive Kentworth has spent her life hiding her interest in architecture, even though she pores over architectural books and sketches buildings. When she accepts a job on a home expansion, it's only because her cousin Amos agrees to pose as the builder. To further hide her involvement, Olive takes a position as a nanny--not knowing that she'll be working for her idol, Joplin's leading architect, widower Maxfield Scott. Maxfield is intrigued by his new nanny--she makes his home and his life bearable again. His work, on the other hand, is a disaster. An untrained builder is remodeling a completed project of his. What's worse, Maxfield's current client wants changes to his plans because of that builder's work.As the architectural one-upmanship heats up, Olive's involvement becomes harder to hide. Will the relationship between her and Maxfield survive, or will they both miss out on building something for their future?"--